Habermas : a very short introduction - Finlayson, James Gordon (Very short introductions, 2005)
This book gives a clear and readable overview of the philosophical work of Jurgen Habermas, the most influential German philosopher alive today, who has commented widely on subjects such as Marxism, the importance and effectiveness of communication, the reunification of Germany, and the European Union. Gordon Finlayson provides readers with a clear and readable overview of Habermas's forbiddingly complex philosophy using concrete examples and accessible language. He then goes on to analyse both the theoretical underpinnings of Habermas's social theory, and its more concrete applications in the fields of ethics, politics, and law; and concludes with an examination how Habermas's social and political theory informs his writing on contemporary, political, and social problems.